Photoelectric Plasticity in Oxide Thin Film Transistors with Tunable Synaptic Functions. (16th October 2018) - Wu, Quantan; Wang, Jiawei; Cao, Jingchen; Lu, Congyan; Yang, Guanhua; Shi, Xuewen; Chuai, Xichen; Gong, Yuxin; Su, Yue; Zhao, Ying; Lu, Nianduan; Geng, Di; et al.
Abstract: Emulating key synaptic functions in electronic devices is quite significant in bioinspired applications. Artificial synaptic thin film transistors (TFT) offer a promising solution for efficient synapse simulation. Herein, artificial synapses based on indium–gallium–zinc oxide (IGZO) TFT are fabricated and the photoelectric plasticity is investigated. Versatile synaptic functions including paired‐pulse facilitation, paired‐pulse depression, and short‐term memory to long‐term memory transition are emulated. More importantly, these synaptic functions can be mediated by modulating the composition ratio of IGZO film. These achievements represent a major advance toward implementation of full synaptic functionality in neuromorphic hardware and the strategy that combines the photonics and the electrics has great prospects in optoelectronic applications. Abstract : Artificial synapses based on the indium–gallium–zinc oxide (IGZO) thin film transistors are fabricated and the photoelectric plasticity is investigated. Furthermore, the synaptic functions can be mediated by modulating the composition ratio of IGZO film. These achievements represent a major advance toward implementation of full synaptic functionality in neuromorphic hardware and open options to modify the synaptic plasticity functions in artificial synapses.